The effectiveness of drug prevention programs among children in schools - Che Rozubi, Norsayyidatina; Anuar, Azad Athahiri; Mohd Daud, Nurul Ain; Jusoh, Ahmad Jazimin; Kee, Pau (International Journal of Public Health Science (IJPHS), 2024)
The problem of discipline and moral decay nowadays in society in Malaysia is very concerning, especially among children and teenagers, as it spreads very fast and keeps being very difficult to deal with. Drug abuse is a big problem that is spreading among the world community and this will have a very bad effect especially the development of human capital. This study aimed to find out the effectiveness of Drug Prevention Programs among children at school. From this Program we want to know the level of awareness, knowledge, skills, and spirituality among children. This study has used quantitative design and is supported by qualitative data. The first phase is a case study that uses the interview with teachers and government anti-drug agency officers who are involved in the implementation of the program. For the second phase of the study, researchers have used the survey method by distributing questionnaires to the recipient subjects, who are primary school students in at-risk states who have been selected to follow the drug prevention program. The results of the survey show that all the indicators of the effectiveness of the participants, namely awareness, knowledge, skills, and spirituality, have a high percentage, with percentage values of 78.0%, 93.4%, 84.2%, and 93.4%. Overall, of the study show that the implementation of the drug prevention program in schools has achieved its objectives, in addition to paying attention to the effectiveness factors as well as the obstacles and weaknesses encountered.